2022
DOI: 10.1097/tp.0000000000004140
|View full text |Cite
|
Sign up to set email alerts
|

A Fourth Dose of COVID-19 Vaccine Does Not Induce Neutralization of the Omicron Variant Among Solid Organ Transplant Recipients With Suboptimal Vaccine Response

Abstract: Background. Humoral responses to coronavirus disease 2019 (COVID-19) vaccines are attenuated in solid organ transplant recipients (SOTRs), necessitating additional booster vaccinations. The Omicron variant demonstrates substantial immune evasion, and it is unknown whether additional vaccine doses increase neutralizing capacity versus this variant of concern (VOC) among SOTRs. Methods. Within an observational cohort, 25 SOTRs with low seroresponse underwent anti–severe acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 16 publications
2
61
0
Order By: Relevance
“…This is particularly important for those who do not mount a robust response to COVID vaccines, given the fact that neutralization of the Omicron variant requires very high levels of antibodies, which may not be routinely achievable even with a fourth dose of mRNA vaccine in transplant recipients. 105 Other recent options for early treatment include 2 oral drugs, nirmatrelvir/ritonavir and molnupiravir (although nirmatrelvir/ritonavir has potentially severe drug-drug interactions), and a 3-d outpatient remdesivir protocol. Convalescent plasma is undergoing a resurgence of interest following recent studies on the early use of high-titer plasma that showed benefit.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for those who do not mount a robust response to COVID vaccines, given the fact that neutralization of the Omicron variant requires very high levels of antibodies, which may not be routinely achievable even with a fourth dose of mRNA vaccine in transplant recipients. 105 Other recent options for early treatment include 2 oral drugs, nirmatrelvir/ritonavir and molnupiravir (although nirmatrelvir/ritonavir has potentially severe drug-drug interactions), and a 3-d outpatient remdesivir protocol. Convalescent plasma is undergoing a resurgence of interest following recent studies on the early use of high-titer plasma that showed benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Concerningly, initial studies suggest that the ‘value-add’ of a fourth vaccine dose may be limited in those with a poor response to a three-dose vaccine series (41, 42). Among SOTRs with a weak serological response to prior vaccine doses, elevated titres of binding and neutralizing antibodies to many variants of concern were noted following a fourth dose; however, neutralization against Omicron was largely unchanged (43). In a KTR cohort, only 10% of previous non-responders after three doses achieved an adequate response following a fourth dose (44).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Israel demonstrated enhanced Omicron neutralization after a 4 th dose of COVID-19 mRNA vaccine in healthy health-care workers [37]. However a study of 25 patients with solid organ transplant recipients showed that the 4 th dose was not effective in inducing Omicron neutralization [38]. Such a study has not been published yet for patients with cancer, making this an unmet need.…”
Section: Discussionmentioning
confidence: 99%